The Effect of Shading Devices on OTTV (Overall Thermal Transfer Value) Value of Office Buildings: Case Study of PT Industri Kapal Indonesia (IKI) Building - Zahari, A. Firman; Mulyadi, Rosady; Jamala, Nurul (ASTONJADRO, 2023)
One of the passive design strategies that effectively reduce the heat load on the building envelope, especially in areas with a large surface area of glass shading Device. The research aims to measure the design influence of shading devices against the value of Overall Thermal Transfer Value (OTTV) buildings. Research using quantitative methods, research done by trying Shading devices with Vertical Models, Horizontal multiple fins, and Egg crates, which have the length and slope provided by the Indonesian National Standard SNI. It tests each design shading measured on an impairment basis OTTV the best and best under 45 Watt/m². The results of the study show that shading devices affect the impairment of OTTV. The longer the shading device and the higher the slope, the more effective it is in blocking incoming radiation through the glass surface. Impairment OTTV existing buildings without a shading device have an initial value of 69.572 W/m2, decreased by 55% to 31.57 W/m2. Shading an egg crate with length120 cm with a slope of 40° is the best shading based on a comparative analysis between vertical louver shading and horizontal multiple fin shading. This is due to shading egg crates being able to respond to the sun in incoming low and high altitude angles to minimize or block radiation that enters through the glass surface.